The blue carbon market in Vietnam: Future development, potential and challenges - Vu, Tan Phuong; Pham, Thu Thuy; Tran, Ngoc My Hoa; Nguyen, Thi Thuy Anh; Nguyen, Thi Van Anh; Tang, Thi Kim Hong (Center for International Forestry Research, 2023)
This report was prepared in response to a request from the Vietnamese government, notably that of the Ministry of Agriculture and Rural Development. Its aim is to provide information on the carbon market in general, but also specifically as it relates to forestry, with a focus on blue carbon. This information is intended to support the government to design and implement high quality blue carbon policies, projects and credits. The report assesses the potential of a blue carbon market in Vietnam, including assessing emissions/carbon accounting for mangroves, peatlands, wetlands, seagrass and tidal marshes. It analyses the existing legal framework, as well as opportunities and challenges for the general carbon market and blue carbon in Vietnam, providing recommendations for how Vietnam should move forward with this market. Our report shows that Vietnam has strongly committed to implementing a ‘net zero’ emission goal by 2050. Forestry and blue carbon ecosystems in Vietnam play an important role in mitigating greenhouse gas emissions, maintaining ecosystem services, and mitigating the impacts of climate change, particularly in coastal areas. Recent government policies on the domestic carbon market open up opportunities to create additional sources of finance for forestry, through mechanisms for exchanging and trading emissions reduction results and carbon credits. However, a number of obstacles currently impede the effective design and implementation of a blue carbon market in Vietnam, including: a lack of clear emission quotas for diverse sectors; a lack of oversight of how to include forest carbon and blue carbon activities in the legal framework; insufficient clarity on who owns carbon rights; and weak capacity to implement blue carbon projects. As well as improving the legal framework, it is also critical to improve blue ecosystem inventories. Currently, the Vietnamese government only pays attention to mangrove areas; the forest inventory system overlooks the high potential of seagrass and tidal marsh areas. Improving these national database and monitoring systems could generate additional benefits from a blue carbon market, while promoting biodiversity conservation and improving local livelihoods.